Survey on the Incidence of Reproductive Disorders in Dairy Cattle - Hyun-Joo Lim; Ho-Beak Yoon; Harim Im; Jihoo Park; Yong-il Cho; Yeon-Seop Jeong; Kwang-Seok Ki; Seok-Ki Im (The Korean Society of Animal Reproduction and Biotechnology, 2015)
Intensive genetic selection has resulted in modern dairy cow with very high milk yields but reduced fertility, due mainly to an increase in reproductive disorders. The study was conducted to estimate the proportion of reproductive disorders among dairy cattle. The factors analyzed were; milk yield, cow parity, periparturient disorders, and reproductive status. The result of this study showed the incidence of reproductive disorders in high yielding dairy cows was prevalent. Repeat breeding was the major postpartum reproductive problem comprising (42.3%) of the samples. Higher reproductive disorders were also associated with lower parity. These disorders subsequently reduced reproductive performance by prolonged intervals from calving to first artificial insemination and from calving to pregnancy. Abnormalities in the reproductive system such as repeat breeder, silent heat, anestrous and ovarian cysts, as well as lower fertility have been recorded during the summer months (June to August). In conclusion, the study revealed that incidence of repeat breeder is mostly prevalent in dairy cows. Moreover, the incidence of reproductive disorders was higher in summer season and hence appropriate preventive and or therapeutic measures as per the type of abnormalities need to be undertaken.